60.9k views
1 vote
Solve the equation 1/3m+6m-9/3m=3m-3/4m

Solve the equation 1/3m+6m-9/3m=3m-3/4m-example-1

1 Answer

4 votes
m
=
0

O
r

m
=
23
15

Step-by-step explanation:
1
3
m
+
6
m

9
3
m
=
3
m

3
4
m




1
+
6
m

9
3
m
=
3
m

3
4
m







8
+
6
m
3
m
=
3
m

3
4
m






(

8
+
6
m
)
×
4
m
=
(
3
m

3
)
×
3
m







32
m
+
24
m
2
=
9
m
2

9
m







32
m
+
24
m
2

9
m
2
+
9
m
=
0






15
m
2

23
m
=
0






m
(
15
m

23
)
=
0



m
=
0



Or


15
m

23
=
0

15
m
=
23

m
=
23
15
User Jagdish Barabari
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.